Beliefs and truth-telling: A laboratory experiment - Ronald Peeters; Marc Vorsatz; Markus Walzl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
We conduct a laboratory experiment with a constant-sum sender-receiver game to investigate the impact of individuals first- and second-order beliefs on truth-telling. While senders are more likely to lie if they expect the receiver to trust their message (which is in line with expected payoff maximization), they are also more likely to tell the truth if they believe the receiver expects them to tell the truth. We observe no such dependence on second-order beliefs in a payoff equivalent game of matching pennies. Our results therefore indicate an impact of second-order beliefs as derived in models of guilt aversion in an antagonistic setting which is specific to strategic information transmission.
Keywords: C70; C91; D03; 330; Experiment; Sender-receiver games; Strategic information transmission; Guilt-from-blame; let-down aversion